Evaluation of employee performance appraisal process in a South African facility management company - Naicker, Seelan (My University, 2012)
Performance appraisal is one element of the performance management process which involves different measurements throughout the organization. But it is the element that is most important if organisations are to take full advantage of their most important asset – employees. The purpose of this research was to evaluate the employee performance appraisal process in a South African facility management company and to suggest recommendations to management based on the literature review. The research took the form of a case study with a sample of 20 respondents who participated in individual qualitative structured interviews. Multiple sources of data were used in the data gathering process and triangulation was achieved by analysing the literature, policies and procedure of Company X as well as data gathered from the individual interviews. The findings of the research revealed that there were numerous gaps in the performance appraisal process, with respondents expressing deep concern on the validity and merits of the current appraisal practices. The main findings showed that respondents thought there was a lack of objectivity in contracts and poor communication. Furthermore the low emphasis on employee training and appraisers’ lack of skills were also raised as issues and concerns on the effectiveness of the appraisal process. The conclusions of the research have informed the main recommendations, to improve the current process to one that is much more effective and which incorporates more interactive communication and training on a continuous basis for both employees and appraisers
MBA thesis - WBS
Keywords: Performance appraisal; Employee performance appraisal